Binary cracking kinetics for thermal cracking of vacuum residues in Eureka process - Mohd Shah, M.S.B. (Elsevier Ltd, 2014)
A discrete lumped kinetic model for thermal cracking of Kuwaiti vacuum residues such as Ratawi-Burgan vacuum residue (RB-VR), Lower-Fars vacuum residue (LF-VR) and Eocene vacuum residue (EC-VR) in the Eureka process is presented. The discrete lumps considered for kinetic modeling of thermal cracking reactions are: (i) off-gases (<423 K), (ii) cracked light oil (423-643 K), (iii) cracked heavy oil (643-811 K), (iv) demister oil (>811 K) and (v) vacuum residue (VR-CCR). In kinetic modeling, the binary thermal cracking reactions between the lumps and reactions which occur within the lumps are considered to determine the time dependent behavior of cracked products. A combination of dynamic global and local combined particle swarm optimization and fourth order Levenberg-Marquardt algorithm is applied to estimate the twenty kinetic parameters included in the kinetic model. The discrete lumped model presented for thermal cracking of vacuum residues in the Eureka process shows good agreement with the experimental data available in the literature for RB-VR, LF-VR and EC-VR. Furthermore, the model validation reveals that the cracking reactions which occur within VR-CCR lump is significant as a result of estimated activation energies in thermal cracking of Kuwaiti vacuum residues over the range of temperature from 673 to 703 K. Â© 2014 Elsevier Ltd. All rights reserved.